Effectiveness of a community-based intervention package in maternal health service utilization: A cross-sectional quasi-experimental study in rural Ghana. - Hirotsugu Aiga; Yoshito Kawakatsu; Nobuhiro Kadoi; Emmanuel Obeng; Frank Tabi Addai; Frederick Ofosu; Kazuki Fujishima; Mayumi Omachi; Etsuko Yamaguchi (PLoS ONE)
Background We examined the effectiveness of a community-based intervention package that targeted pregnant women for increasing utilization of maternal health services. The intervention package was implemented in Suhum Municipality, Ghana, from March 2019 to April 2022. The package consisted of: (i) maternal health education by female and male peers; (ii) training existing health workers on maternal health; and (iii) strengthening the local community health management committees. Methods A cross-sectional household survey was conducted in May 2022. We sampled four groups of women: (i) intervention at baseline; (ii) intervention at follow-up; (iii) control at baseline; and (iv) control at follow-up. Three outcome variables were set, i.e., the proportions of women having utilized: (i) at least four antenatal care (ANC) services; (ii) facility-based delivery (FBD) services; and (iii) post-partum care (PPC) services. To estimate the effectiveness of the intervention package in increasing the service coverages, both crude and adjusted difference-in-differences (DID) estimates were calculated. Significance levels were set at the values of 0.10, 0.05, and 0.01, since the aforementioned service coverages had already been too high to have room for an increase at the significance level of 0.05. Results The proportion of women completing at least four ANC services displayed significant DID in both crude and adjusted analyses. The proportions of women utilizing facility-based delivery services and post-partum care services did not display significant DID. Conclusions Of the three outcome variables set, only the proportion of women having utilized at least four ANC services significantly increased in the intervention group, compared with the control group. Ghana has been in the transition process of shifting the minimum number of ANC visits from four to eight. Thus, nationwide scaling up of the intervention package is expected to help the transition be smooth by increasing the number of ANC visits.